Self-reported perception of statistical literacy: Evidence from a National Survey of U.S. Adults - Samuel Anyaso-Samuel; Mark Louie Ramos (PLoS ONE, 2026)
Amid growing recognition of the role statistical literacy plays in informed decision-making, we examined self-reported statistical literacy and willingness to apply statistical reasoning in everyday contexts using data if they understood statistics better through secondary data analysis of a nationally representative survey of U.S. adults. The survey showed that 62% of U.S. adults self-report having little to no idea what statistics or statistical concepts like p-values are, but 90% of them would base decisions on reported statistics at least sometimes if they understood them better. Survey-weighted ordinal regression revealed that higher educational attainment was positively associated with perceived statistical literacy, while older generational cohorts reported lower levels. Individuals who rated themselves as more statistically literate expressed greater willingness to use statistical information provided they understood it better. These findings highlight the urgent need to further expand statistical education across both formal curricula and informal learning environments to empower public engagement with data-driven issues.